2021
DOI: 10.1063/5.0070603
|View full text |Cite
|
Sign up to set email alerts
|

Mass ratio effect on vortex-induced vibration for two tandem square cylinders at a low Reynolds number

Abstract: A numerical simulation study is conducted to investigate the effect of the mass ratio (m* = 3, 10, and 20) on vortex-induced vibration (VIV) of two tandem square cylinders at Re = 150. In this study, we mainly focus on the mass ratio effect on the vibration response, force characteristics, wake mode pattern, and fluid–structure-interaction (FSI) mechanism. The results show that mass ratio plays an important role in the VIV response of the two cylinders. With increasing reduced velocity, both the upstream cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is worth highlighting that Gu et al. (2023) also studied the effect of on 2-DOF vibrations of tandem square cylinders at and observed qualitatively similar and variation. In their study, the peaks of and are also close to the peaks and of the present study, even though the cross-sections are significantly different.…”
Section: Characteristics Of Cylinder Vibrationsmentioning
confidence: 69%
“…It is worth highlighting that Gu et al. (2023) also studied the effect of on 2-DOF vibrations of tandem square cylinders at and observed qualitatively similar and variation. In their study, the peaks of and are also close to the peaks and of the present study, even though the cross-sections are significantly different.…”
Section: Characteristics Of Cylinder Vibrationsmentioning
confidence: 69%
“…(2016) and Qiu et al . (2021 b ), as shown in figure 3.
Figure 3.Comparison of the VIV results of a square cylinder with m * = 3 and ξ = 0 at Re = 100.
…”
Section: Numerical Methods For Cfd Simulationmentioning
confidence: 96%
“…The present DNS model is benchmarked first against available results reported in the literature for a single square cylinder undergoing two-degree-of-freedom VIV with m* = 3 and ξ = 0 at Re = 100 and U r = 3-16. The calculated results versus U r , involving the cross-flow amplitude and frequency, are compared with those from Zhao, Cheng & Zhou (2013), Jaiman et al (2016) and Qiu et al (2021b), as shown in figure 3.…”
Section: Numerical Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow-induced vibration (FIV) and vortex-induced vibration (VIV) are crucial research subjects for the flow characteristics of two tandem square cylinders. Qiu et al [14] used numerical simulations to study the influence of variables on the VIV of two tandem square cylinders under the condition of Re = 150 and mass ratios (m*) of 3, 10, and 20, respectively. They reported that the mass ratio has an important influence on the vortex-induced vibration response of the double cylinders, and the mass ratio has a great influence on the distance between the two cylinders.…”
Section: Introductionmentioning
confidence: 99%